Performance evaluation of high performance concrete beams under cyclic loading - Sharmila, S.; Chandrasekaran, P. (International Journal of Engineering and Technology, 2017)
High performance concrete essentially consists of the same ingredients as in conventional concrete but the proportions are designed to provide the strength and durability which are needed for the structural and environmental requirements of the structure. Fiber-reinforced concrete is a concrete containing ingredients of conventional concrete and fibres which increases its structural integrity. Fibers act as crack arrester which are primarily due to plastic shrinkage and drying shrinkage. They also reduce the permeability of concrete. The main aim of the present experimental investigation is to combine different fibres namely crimped stainless steel fibre and Aramid fibre to produce HFRC and thus to evaluate its mechanical performance. In Addition Micro silica and Quartz powder is added to obtain high performance. Based on I.S. Code method of mix design, proportion of different ingredients was obtained to get M60 grade concrete. Samples were prepared by varying the volume fraction of Steelfibre and aramid fibre from 0 to 1.5%. Three specimens of Cubes, Cylinders, and Prisms for each volume fraction of fibers are casted. Mechanical properties of each concrete composite were studied. The structural parameters such as load carrying capacity, ductility characteristics and energy absorption capacity of HPHFRC beams were assessed.